Morphological and semantic opacity as factors of linguistic change: A study of Form VIII verbs in Arabic - Ech-Charfi, Ahmed (Lingua Posnaniensis, 2026)
This paper deals with the role of morphology in the reconstruction of lexical meaning. It focuses on the case of the Arabic Form VIII verbs in order to illustrate the challenge that morpho-semantics presents for historical lexicographers assuming the unity of a language throughout a long period of its use. In this connection, the paper attempts to show that, although Form VIII verbs have been in use since the early stages of Arabic, it is likely that users assigned them different meanings according to whether Form VIII morpho-semantics was transparent or opaque. Three factors have been identified that increase the opacity of this category: allomorphy, polysemy and frequency of the derivation base. 529 items were culled from a bilingual dictionary for the purposes of the study, and allomorphy was found to contribute about 12% to morphological opacity, and more than 70% of the verbs had a non-prototypical sense. Many of the extended senses seem to have lost all kinds of semantic relation to the prototypical sense, thus resulting in less transparency in the semantics of the derived forms. The study also argues that the less frequent the base of the derivation is, the more opaque Form VIII will be. The paper concludes that, given the lack of rich data from the early stages of Arabic, it is likely that a satisfactory reconstruction of the meaning of derived forms will probably never be achieved.